Lithium nickel manganese oxide positive electrode material, preparation method thereof and electrochemical device

By doping M and N elements into the Ni-Manganate Lithium Manganate positive electrode material and wet coating using titanium aluminum phosphate, the problems of low lithium ion transmission rate and poor rate performance of the material are solved, and gas production is reduced and performance improvement is achieved.

CN119833620APending Publication Date: 2025-04-15NANTONG RESHINE NEW MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510125242.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing lithium nickel manganate positive electrode materials have problems such as low lithium ion transmission rate and poor rate performance.

Method used

During the preparation of the nickel-manganate positive electrode material, the matrix material is doped and modified by using M elements and N elements, and wet coated with titanium aluminum phosphate to form a thin, uniform and dense coating layer.

Benefits of technology

It effectively reduces the gas production of the nickel-manganese oxide cathode material, improves its circulation and rate performance, and improves the structural stability and lithium ion transmission rate of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833620A_ABST
    Figure CN119833620A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium nickel manganese oxide positive electrode material, a preparation method thereof and an electrochemical device, the preparation method comprises: mixing a nickel source, a manganese source, a first compound, a second compound and a lithium source to obtain a first mixture, the first compound containing an element M, the M being a tetravalent or pentavalent transition metal element, the second compound containing an element N, and the lithium source being a tetravalent or pentavalent transition metal element; n is a divalent or trivalent transition metal element, and M and N can respectively form strong chemical bonds with oxygen; performing first heat treatment on the first mixture to obtain a base material; carrying out wet mixing on the base material and lithium titanium aluminum phosphate, and carrying out spray drying to obtain a second mixture; and performing second heat treatment on the second mixture to form a coating layer containing lithium titanium aluminum phosphate on the surface of the matrix material, thereby obtaining the lithium nickel manganese oxide positive electrode material. The rate capability, the cycle performance and the structural stability of the lithium nickel manganese oxide positive electrode material are jointly improved through the synergistic effect of the doped elements and the wet-process coated lithium titanium aluminum phosphate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery materials technology, specifically to lithium nickel manganese oxide cathode materials, their preparation methods, and electrochemical devices. Background Art

[0002] High power and high energy density are key factors for the application of lithium-ion batteries in hybrid electric vehicles and plug-in hybrid electric vehicles. In recent years, the exploration of cathode materials with high power and high energy density to improve the performance of lithium-ion batteries has attracted much attention. The charge-discharge platform of traditional lithium manganese oxide, lithium cobalt oxide, and lithium iron phosphate cathode materials is usually only 4V, while the charge-discharge platform voltage of lithium nickel manganese oxide cathode material reaches 4.7V, and it has superior properties such as low cost, environmental friendliness, and good thermal stability.

[0003] However, existing lithium nickel manganese oxide cathode materials still suffer from problems such as low lithium-ion transport rate and poor rate performance. Summary of the Invention

[0004] In view of this, in order to solve at least one of the above technical problems, the present application provides a method for preparing a lithium nickel manganese oxide positive electrode material.

[0005] In addition, this application also provides a lithium nickel manganese oxide cathode material prepared by the aforementioned method for preparing lithium manganese oxide cathode material, and an electrochemical device using the lithium manganese oxide cathode material.

[0006] In a first aspect, an embodiment of the present application provides a method for preparing a lithium nickel manganese oxide positive electrode material, the preparation method comprising the following steps: A nickel source, a manganese source, a first compound, a second compound, and a lithium source are mixed to obtain a first mixture. The first compound contains element M, which is a transition metal element with a tetravalent or pentavalent ionic state, and the bond energy of the chemical bond formed by element M and oxygen is 350 kJ / mol to 800 kJ / mol. The second compound contains element N, which is a transition metal element with a divalent or trivalent ionic state, and the bond energy of the chemical bond formed by element N and oxygen is 350 kJ / mol to 800 kJ / mol. performing a first heat treatment on the first mixture to obtain a matrix material; Wet-mixing the matrix material with lithium aluminum titanium phosphate, and spray-drying the mixture to obtain a second mixture; and The second mixture is subjected to a second heat treatment to form a coating layer on the surface of the base material, wherein the chemical formula of the coating layer is Li. 1+z Al z Ti 2-z(PO4)3, where 0.2 ≤ z ≤ 0.4, thereby obtaining the lithium nickel manganese phosphate cathode material.

[0007] In some possible embodiments, the stirring frequency of the wet mixing is 10 Hz to 50 Hz; and / or The stirring time of the wet mixing is 0.5 h to 10 h.

[0008] In some possible embodiments, the spray drying satisfies at least one of the following conditions: (1) The spray speed of the spray drying is 1 L / h to 10 L / h; (2) The temperature of the spray drying is 250 °C to 300 °C; (3) The nozzle pressure of the spray drying is 0.05 MPa to 0.2 MPa; (4) The nozzle diameter of the spray drying is 0.5 mm to 2 mm.

[0009] In some possible embodiments, the mass ratio of the matrix material to the lithium aluminum titanium phosphate is (0.1 to 5):1.

[0010] In some possible embodiments, the general formula of the matrix material is Li(Li a Ni y Mn x M b N c )O 4-δ , where 0.02 ≤ a ≤ 0.06, 0.04 ≤ b ≤ 0.20, 2 ≤ b / a ≤ 10 / 3, 0 < c ≤ 0.1, 0.4 ≤ y ≤ 0.55, 1.3 ≤ x ≤ 1.6, 0.0001 ≤ δ ≤ 0.05, a + m×b + n×c + 2y + 4x = 7, m is the ionic valence state of the M element, and n is the ionic valence state of the N element.

[0011] In some possible embodiments, the conditions of the second heat treatment include: the atmosphere includes an air atmosphere with an atmosphere pressure greater than atmospheric pressure by 0.05 MPa to 0.2 MPa, the temperature is 650 °C to 750 °C, and the time is 6 h to 12 h.

[0012] In some possible embodiments, the preparation method of the lithium aluminum titanium phosphate includes: Mixing an Al compound, a Ti compound, a P compound, and a Li compound and performing spray drying to obtain a coated material precursor; and Performing a third heat treatment on the coated material precursor to obtain the lithium aluminum titanium phosphate.

[0013] Second aspect, the embodiments of the present application further provide a lithium nickel manganese oxide cathode material. The lithium manganese oxide cathode material is prepared by the preparation method of the lithium nickel manganese oxide cathode material described above. The lithium nickel manganese oxide cathode material includes a matrix material and a coating layer located on the surface of the matrix material. The matrix material is lithium nickel manganese oxide containing M element and N element. Among them, M element is a transition metal element with an ionic valence state of tetravalent or pentavalent, and the bond energy of the chemical bond formed by M element and oxygen is 350 kj / mol to 800 kj / mol. N element is a transition metal element with an ionic valence state of divalent or trivalent, and the bond energy of the chemical bond formed by N element and oxygen is 350 kj / mol to 800 kj / mol. The chemical general formula of the coating layer is Li 1+z Al z Ti 2-z (PO4)3, where 0.2 ≤ z ≤ 0.4.

[0014] In some possible embodiments, the thickness of the coating layer is 5 nm to 80 nm; and / or The charge transfer resistance value of the lithium nickel manganese oxide cathode material is 15 Ω to 50 Ω.

[0015] In some possible embodiments, the chemical general formula of the matrix material is Li(Li a Ni y Mn x M b N c )O 4-δ , where 0.02 ≤ a ≤ 0.06, 0.04 ≤ b ≤ 0.20, 2 ≤ b / a ≤ 10 / 3, 0 < c ≤ 0.1, 0.4 ≤ y ≤ 0.55, 1.3 ≤ x ≤ 1.6, 0.0001 ≤ δ ≤ 0.05, a + m×b + n×c + 2y + 4x = 7, m is the ionic valence state of M element, and n is the ionic valence state of N element. [[ID=2​​​​​​The reduced content of [unspecified substance] lowers the risk of the Ginger-Taylor effect, thus effectively reducing the gas production of lithium nickel manganese oxide cathode materials and improving their cycle performance. On the other hand, by using highly conductive lithium titanium aluminum phosphate for wet coating of the substrate material, a thin, uniform, and dense coating layer is formed, providing more effective protection for the substrate material and acting as a physical and chemical barrier. This reduces the dissolution of dopants M and N from the substrate material and improves the interfacial stability and lithium-ion transport rate between the lithium nickel manganese oxide cathode material and the electrolyte, thereby enhancing the rate performance of the lithium nickel manganese oxide cathode material.

[0018] This application combines elemental doping with wet coating of lithium titanium aluminum phosphate. Elemental doping can effectively improve the stability of the surface spinel structure of lithium nickel manganese oxide, while wet-coated lithium titanium aluminum phosphate can be uniformly and densely bonded with the surface spinel structure of lithium nickel manganese oxide, synergistically achieving a joint improvement in the rate performance, cycle performance and structural stability of lithium nickel manganese oxide cathode material. Attached Figure Description

[0019] Figure 1 This is a process flow chart of the preparation method of the lithium nickel manganese oxide positive electrode material provided in an embodiment of the present application.

[0020] Figure 2 This is a comparative schematic diagram of wet coating and dry coating provided in the embodiments of this application.

[0021] Figure 3 This is a SEM image of the lithium nickel manganese oxide cathode material prepared in Example 1 of this application.

[0022] Figure 4 This is a SEM image of the lithium nickel manganese oxide cathode material prepared in Comparative Example 4 of this application.

[0023] Figure 5 This is a SEM image of the lithium nickel manganese oxide cathode material prepared in Comparative Example 5 of this application.

[0024] Figure 6 XRD diffraction patterns of the lithium nickel manganese oxide positive electrode materials prepared in Examples 1-3 and Comparative Examples 1-5 of the present application. DETAILED DESCRIPTION

[0025] Embodiments of the present application will be described in detail below. The embodiments described below by referring to the accompanying drawings are exemplary and are only used to explain the present application, and should not be construed as a limitation to the present application. It should be noted that unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the technical field to which the present application belongs. Without conflict, the embodiments of the present application and the features in the embodiments can be combined with each other. Many specific details are set forth in the following description to facilitate a thorough understanding of the present application. The described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments.

[0026] Please refer to Figure 1 As shown, the embodiments of the present application provide a preparation method of a lithium nickel manganese oxide cathode material, which specifically includes the following steps: Step S1, mixing a nickel source, a manganese source, a first compound, a second compound and a lithium source to obtain a first mixture, wherein the first compound contains an M element, the M element is a transition metal element with an ionic valence of tetravalent or pentavalent, and the bond energy of the chemical bond formed by the M element and oxygen is 350 kj / mol to 800 kj / mol, the second compound contains an N element, the N element is a transition metal element with an ionic valence of divalent or trivalent, and the bond energy of the chemical bond formed by the N element and oxygen is 350 kj / mol to 800 kj / mol.

[0027] Specifically, mix the nickel source, the manganese source, the first compound, the second compound and the lithium source, and use a horizontal rod pin type sand mill for pulverization. Liquid phase media such as water and dispersant can also be added to the pulverized raw materials for wet mixing to obtain a first mixture. At the same time, the doping amounts of the first compound and the second compound in the first mixture can be further adjusted.

[0028] In some embodiments, the nickel source, the manganese source, the first compound, the second compound and the lithium source can be mixed in a molar ratio of y:x:b:c:(1 + a), wherein 0.02 ≤ a ≤ 0.06, 0.04 ≤ b ≤ 0.20, 2 ≤ b / a ≤ 10 / 3, 0 < c ≤ 0.1, 0.4 ≤ y ≤ 0.55, 1.3 ≤ x ≤ 1.6, a + m×b + n×c + 2y + 4x = 7, m is the ionic valence of the M element, and n is the ionic valence of the N element.

[0029] In some embodiments, M can include at least one of Ti, Zr, Nb, etc. The first compound can include at least one of the corresponding carbonate, hydroxide, oxide, etc. of M.

[0030] In some embodiments, N can include at least one of Mg, Al, etc. The second compound can include at least one of the corresponding carbonate, hydroxide, oxide, etc. of N.

[0031] In some embodiments, the dispersant may include at least one of ethanol, acetone, isopropanol, etc.

[0032] In some embodiments, the particle size D50 of the first mixture may be 0.1 μm to 2 μm, which is beneficial to the formation of a single-crystalline lithium nickel manganese oxide cathode material, thereby further improving the rate performance and mechanical strength of the lithium nickel manganese oxide cathode material. Exemplarily, the particle size D50 of the first mixture may be 0.1 μm, 0.2 μm, 0.3 μm, 0.5 μm, 0.7 μm, 0.9 μm, 1.0 μm, 1.3 μm, 1.5 μm, 1.7 μm, 2.0 μm or any value within the range composed of any two of the above values.

[0033] In some embodiments, the lithium source includes at least one of lithium hydroxide, lithium carbonate, lithium nitrate, etc.

[0034] In some embodiments, the manganese source includes at least one of manganese dioxide and manganese tetroxide, etc.

[0035] In some embodiments, the nickel source includes at least one of nickel hydroxide, nickel carbonate, nickel nitrate, nickel oxyhydroxide, etc.

[0036] Step S2: Perform a first heat treatment on the first mixture to obtain a matrix material.

[0037] Specifically, perform a first heat treatment on the mixture under certain atmosphere and sintering conditions, and perform crushing, classification, and sieving to obtain a matrix material of lithium nickel manganese oxide with a spinel structure. The chemical general formula of this matrix material is Li(Li a Ni y Mn x M b N c )O 4-δ , where 0.02 ≤ a ≤ 0.06, 0.04 ≤ b ≤ 0.20, 2 ≤ b / a ≤ 10 / 3, 0 < c ≤ 0.1, 0.4 ≤ y ≤ 0.55, 1.3 ≤ x ≤ 1.6, 0 ≤ δ ≤ 0.05, a + m×b + n×c + 2y + 4x = 7, m is the ionic valence state of element M, and n is the ionic valence state of element N.

[0038] The matrix material is doped with specific elements M and N to modify the matrix material. Elements M and N replace Mn to occupy the 16d site, reducing the content of Mn with the Jahn-Teller effect 3+ , effectively reducing the gas generation amount of the lithium nickel manganese oxide cathode material and improving the cycle performance of the lithium nickel manganese oxide cathode material. In addition, elements M and N can form strong chemical bonds with oxygen, enhancing the structural stability of the matrix material. At the same time, controlling the doping amounts of M and N elements can better maintain the stability of the spinel phase of the matrix material.

[0039] Specifically, in the chemical general formula of the matrix material: a represents the doping amount of Li in the matrix material. By appropriately doping Li at the 16d position of Mn, the power, cycle performance, and storage (low gas generation) performance of the lithium nickel manganese oxide cathode material can be improved. Specifically, the range of the doping amount of Li is 0.02 ≤ a ≤ 0.06, and further it can be 0.02 ≤ a ≤ 0.05. Exemplarily, a can be 0.02, 0.03, 0.04, 0.05, 0.06, or any value within the range formed by any two of the above values.

[0040] b represents the content of M in the matrix material. Appropriate doping of the M element can significantly reduce the gas generation amount of the lithium nickel manganese oxide cathode material and improve the cycle performance of the lithium nickel manganese oxide cathode material. Specifically, the range of the doping amount of M is 0.04 ≤ b ≤ 0.20, and further it can be 0.04 ≤ b ≤ 0.1. Exemplarily, b can be 0.04, 0.06, 0.08, 0.1, 0.15, 0.2, or any value within the range formed by any two of the above values. If the doping amount of the M element is too high (b > 0.2), it may cause a decrease in the discharge capacity, and if it is too low (b < 0.04), it may not achieve an effective doping modification effect.

[0041] At the same time, by controlling the doping ratio b / a of M to Li within the range of 2 ≤ b / a ≤ 10 / 3, the molar ratio of M to Li at the 16d site can be controlled within the above range, which can better maintain the stability of the matrix material, inhibit the dissolution of manganese, and the gas generation amount. Further, this ratio can also be 2 ≤ b / a ≤ 3. Exemplarily, b / a can be 2, 2.4, 2.6, 2.8, 3.0, 10 / 3, or any value within the range formed by any two of the above values.

[0042] c represents the content of N in the matrix material. Appropriate doping of the N element is beneficial to replace Mn and / or part of Ni, effectively improving the cycle performance and storage performance (low gas generation) of the matrix material. The range of c can be 0 < c ≤ 0.1, and further it can be 0.01 ≤ c ≤ 0.04. Exemplarily, c can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.​​x represents the Mn content in the matrix material. The Mn content range is 1.3 ≤ x ≤ 1.6, which can increase the material capacity, improve the material structural stability, and enhance the material conductivity. x can further be 1.35 ≤ x ≤ 1.5. For example, x can be 1.3, 1.35, 1.37, 1.39, 1.4, 1.43, 1.47, 1.5, 1.55, 1.58, 1.6, or any value within the range of any two of the above values.

[0044] y represents the Ni content in the matrix material. The Ni content range is 0.4 ≤ y ≤ 0.55, which can improve the capacity of the matrix material in the high discharge potential region (> 4.1 V). y can further be 0.4 ≤ y ≤ 0.5. For example, y can be 0.4, 0.42, 0.44, 0.45, 0.46, 0.48, 0.5, 0.52, 0.54, 0.55, or any value within the range formed by any two of the aforementioned values.

[0045] Moreover, a+m×b+n×c+2y+4x=7, where m is the ionic valence of the M element and n is the ionic valence of the N element. This is to ensure that the matrix material still satisfies the chemical valence balance after being doped with metal elements, while satisfying the structural ratio of the spinel structure AB2O4, reducing the structural degradation of the matrix material during the cycle, and thus improving the structural stability and cycle stability of the matrix material.

[0046] "4-δ" indicates that oxygen defects may be present. Specifically, δ is 0.0001≤δ≤0.04. Due to the presence of possible oxygen defects, a certain amount of trivalent Mn is contained, resulting in a disordered arrangement of transition metal ions. This disordered spinel The ion diffusion rate in the material is two orders of magnitude higher than that of ordered spinel (P4332), and it has higher capacity and rate performance. However, trivalent Mn can trigger the Jahn-Teller effect, causing drastic structural changes in the lithium nickel manganese oxide cathode material and accelerating the destruction of the lithium nickel manganese oxide cathode material structure.

[0047] In some embodiments, the first heat treatment may include sintering, wherein the sintering atmosphere may be an atmospheric atmosphere with a pressure greater than atmospheric pressure by 0.05 MPa to 0.20 MPa. Further, the sintering may be a two-stage sintering, comprising a first stage sintering and a second stage sintering performed sequentially: the first stage sintering temperature may be 750–950 °C, and the first stage sintering time may be 6–20 h; the second stage sintering temperature may be 500–700 °C, and the second stage sintering time may be 4–15 h, wherein the cooling rate from the first temperature to the second temperature is less than or equal to 4 °C / min.

[0048] By employing a two-stage sintering process, the first stage of sintering is carried out at a high temperature of 750℃ to 950℃. Increasing the sintering temperature promotes ion migration and increases grain growth rate. Then, a second stage of sintering is performed at a cooling rate of 4℃ / min to 500℃ to 700℃. Due to the presence of disordered crystalline phases, low-temperature annealing allows for oxygen repair, correcting surface defects and oxygen defects in the bulk matrix material. This also increases the proportion of the high-voltage plateau, i.e., the shoulder capacity ratio. Furthermore, annealing allows fragments detached from the particle surface during the pulverization process to be remelted, improving the capacity and cycle life of the lithium battery. Additionally, the cooling rate should not be too fast; a slow cooling rate of 4℃ / min allows for sufficient oxygen repair and reduces the adverse effects of internal stress accumulation caused by rapid external temperature changes, improving the rate performance and cycle life of the matrix material.

[0049] In some embodiments, the crushing method may include at least one of air jet milling and mechanical milling to disperse and refine the matrix material particles.

[0050] In some embodiments, the particle size D50 of the matrix material can be 4 μm to 12 μm, which is beneficial for improving the control of the particle size of the lithium nickel manganese oxide cathode material, enabling the lithium nickel manganese oxide cathode material to have a suitable specific surface area and compaction density. The particle size D50 of the matrix material can further be 4 μm to 9 μm. The particle size D50 of the matrix material can exemplary be 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, or any value within the range of any two of the above values.

[0051] In some embodiments, prior to the heat treatment step of the first mixture, the preparation method may further include drying the first mixture by spray drying. Spray drying removes moisture from the first mixture, effectively preventing agglomeration during heat treatment and improving the efficiency of the heat treatment process. Furthermore, the moisture weight percentage of the first mixture after spray drying can be controlled to be less than or equal to 1 wt%.

[0052] Step S3: The matrix material is wet-mixed with lithium aluminum titanium phosphate, and the mixture is spray-dried to obtain a second mixture.

[0053] Specifically, water and / or dispersants or other liquid media are added to the matrix material and lithium titanium aluminum phosphate for wet mixing to form a slurry. The uniformly mixed slurry is then spray-dried using a spray dryer to achieve wet coating, thereby obtaining a second mixture.

[0054] Among them, the wet mixing method may include mixing, stirring or grinding with a high-speed mixer, etc., which can effectively mix the matrix material and lithium titanium aluminum phosphate. Compared with dry mixing, the slurry obtained by wet mixing can improve the uniformity of the mixing of the matrix material and lithium titanium aluminum phosphate under the action of the liquid medium, which is conducive to achieving uniform coating of the matrix material by lithium titanium aluminum phosphate. After wet mixing, the slurry is spray-dried to achieve wet coating to obtain a second mixture. By spraying the liquid slurry into fine droplets, the water or dispersant is quickly evaporated in the high-temperature airflow, thereby forming dry second mixture particles. Spray drying can produce particles with uniform and controllable particle size, and can also effectively remove the liquid component in the slurry, reduce the risk of agglomeration of the second mixture, and help improve the uniformity of coating.

[0055] See also Figure 2 As shown, compared with the point-shaped, island-shaped, overly thick or uneven coating layer formed by dry coating, the coating layer formed by wet coating after sintering has the advantages of thinner thickness, uniformity and density, good coating effect, and can provide more effective protection for the matrix material, acting as a physical and chemical barrier, improving the interface stability and lithium ion transfer rate between the lithium nickel manganese oxide positive electrode material and the electrolyte, thereby improving the rate performance of the lithium nickel manganese oxide positive electrode material.

[0056] In some embodiments, the stirring frequency of the wet mixing is 10 Hz to 50 Hz, and the stirring time of the wet mixing is 0.5 h to 10 h, which is conducive to sufficient mixing to form a uniformly dispersed mixture.

[0057] In some embodiments, the dispersant may include at least one of ethanol, acetone, and isopropanone.

[0058] In some embodiments, the temperature of spray drying can be 250°C to 300°C. The temperature of spray drying is a key factor affecting drying efficiency and product quality. Limiting the temperature of spray drying to the aforementioned range can increase the evaporation rate of the liquid, accelerate the drying process, and will not cause adverse phenomena such as particle melting. The temperature of spray drying can illustratively be 250°C, 255°C, 260°C, 265°C, 270°C, 275°C, 280°C, 285°C, 290°C, 300°C or any value within the range consisting of any two of the above values. The temperature of spray drying can further be 265°C to 280°C.

[0059] In some embodiments, the spray drying spray rate can be 1L / h~10L / h. The spray rate can directly affect the particle size and atomization effect of the droplets. By limiting the spray drying spray rate to the aforementioned range, the slurry can be formed into uniform small droplets during the spraying process, rapidly evaporated at high temperatures, improved drying efficiency, and reduced agglomeration or uneven drying. The spray drying spray rate can illustratively be 1L / h, 2L / h, 3L / h, 4L / h, 5L / h, 6L / h, 8L / h, 9L / h, 10L / h or any value within the range composed of any two of the above values. The spray drying spray rate can further be 2L / h~4L / h.

[0060] In some embodiments, the nozzle pressure of the spray drying can be 0.05 MPa to 0.20 MPa, which can further enhance the atomization effect of the slurry, disperse the slurry into fine droplets, improve the drying efficiency, and facilitate the formation of particles of the second mixture with a smaller particle size. The nozzle pressure of the spray drying can illustratively be 0.05 MPa, 0.075 MPa, 0.10 MPa, 0.125 MPa, 0.150 MPa, 0.175 MPa, 0.20 MPa, or any value within the range of any two of the above values. The nozzle pressure of the spray drying can further be 0.10 MPa to 0.15 MPa.

[0061] In some embodiments, the diameter of the spray drying nozzle can be 0.5 mm to 2 mm, which allows the slurry to be sprayed smoothly, forming smaller droplets, which is conducive to further forming dried particles of the second mixture with smaller particle size. The diameter of the spray drying nozzle can be 0.5 mm, 0.7 mm, 0.9 mm, 1.1 mm, 1.5 mm, 1.7 mm, 2.0 mm, or any value within the range of any two of the above values. The diameter of the spray drying nozzle can further be 0.7 mm to 1.5 mm.

[0062] The nozzle pressure and diameter together control the size and uniformity of the formed droplets. By comprehensively adjusting the nozzle pressure and diameter, the spray coating effect can be improved, forming a second mixture with moderate particle size and uniform particle size distribution.

[0063] Furthermore, after drying by spray drying, the water weight percentage of the second mixture can be controlled to be less than or equal to 1 wt %.

[0064] In some embodiments, the mass ratio of the matrix material to lithium titanium aluminum phosphate is (0.1~5):1. By controlling the mass ratio of the matrix material to lithium titanium aluminum phosphate within the aforementioned range, the coating amount can be effectively controlled, so that lithium titanium aluminum phosphate can effectively protect the matrix material while ensuring that the capacity of the lithium nickel manganese oxide cathode material is not affected.

[0065] In some embodiments, the average particle size D50 of lithium titanium aluminum phosphate is 0.5 μm to 4 μm. Using lithium titanium aluminum phosphate with the aforementioned average particle size range as the coating material of the matrix material is beneficial to reduce the aggregation of lithium titanium aluminum phosphate particles, thereby facilitating uniform coating on the surface of the matrix material.

[0066] The preparation method for mixed and coated lithium aluminum titanium phosphate may specifically include the following steps: Step S31, mixing an Al-containing compound, a Ti-containing compound, a P-containing compound, and a Li-containing compound and spray-drying the mixture to obtain a coating material precursor; and Step S32: heat-treating the coating material precursor to obtain lithium aluminum titanium phosphate.

[0067] In some embodiments, the mixture containing Al, Ti, P and Li compounds can be further crushed. The crushing method is preferably to use a wet pulverizer to refine the particles and further mix them evenly. During the pulverization, it is preferable to add water and / or a dispersant or other liquid medium for wet mixing to obtain a slurry.

[0068] In some embodiments, the average particle size D50 of the pulverized slurry may be 0.1 μm to 2 μm, which is beneficial for improving the particle morphology and quality during the spray drying process while increasing the drying efficiency.

[0069] In some embodiments, the weight percentage of water in the coating material precursor obtained after spray drying can be controlled to be less than or equal to 1 wt %.

[0070] In some embodiments, the conditions for heat treatment of the coating material precursor are as follows: the atmosphere can be an atmospheric atmosphere with a pressure greater than atmospheric pressure by 0.12~0.20 MPa; the heat treatment temperature can be 500℃~800℃; the heat treatment time can be 6h~12h; and the lithium titanium aluminum phosphate is naturally cooled with the furnace after the heat treatment is completed.

[0071] In some embodiments, the lithium aluminum titanium phosphate obtained by heat treatment may be crushed, and the crushing method is preferably air flow crushing.

[0072] In some embodiments, the Li-containing compound includes at least one of lithium hydroxide, lithium carbonate, and lithium nitrate.

[0073] In some embodiments, the Al-containing compound includes at least one of a carbonate, a hydroxide, and an oxide of the Al element.

[0074] In some embodiments, the Ti-containing compound includes at least one of a carbonate, a hydroxide, and an oxide of Ti.

[0075] In some embodiments, the phosphoric acid contains the P compound, preferably an 85% industrial-grade phosphoric acid solution.

[0076] Step S4, performing a second heat treatment on the second mixture to form a coating layer on the surface of the base material to obtain a lithium nickel manganese oxide positive electrode material, wherein the coating layer is lithium titanium aluminum phosphate, and the chemical formula of the coating layer is Li 1+z Al z Ti 2-z (PO4)3, 0.2≤z≤0.4.

[0077] Specifically, the second mixture of lithium titanium aluminum phosphate and the base material is subjected to a second heat treatment to form a lithium titanium aluminum phosphate coating layer on the surface of the base material, and then crushed, classified, and sieved to obtain a lithium nickel manganese oxide positive electrode material, wherein the chemical formula of the coating layer is Li 1+z Al z Ti 2-z (PO4)3, 0.2≤z≤0.4.

[0078] In step S3, lithium aluminum titanium phosphate is coated on the surface of the base material by a wet coating method. The coating layer formed after heat treatment is thin, uniform and dense, which can provide more effective protection for the base material, act as a physical and chemical barrier, and improve the interface stability and lithium ion transfer rate between the lithium nickel manganese oxide positive electrode material and the electrolyte, thereby improving the rate performance of the lithium nickel manganese oxide positive electrode material.

[0079] Moreover, the bulk doping of elements in the matrix material can effectively improve the stability of the surface spinel structure of lithium nickel manganese oxide, and the wet-coated lithium aluminum titanium phosphate can be evenly and densely combined with the surface spinel structure of lithium nickel manganese oxide, synergistically improving the structural stability of the lithium nickel manganese oxide positive electrode material.

[0080] The chemical formula of the coating layer is Li 1+z Al z Ti 2-z In (PO4)3, z represents the Al content in the coating layer. 0.2≤z≤0.4 gives lithium aluminum titanium phosphate (LATP) materials higher ionic conductivity.

[0081] In some embodiments, the conditions for the second heat treatment may include: an atmosphere having a pressure 0.05 MPa to 0.2 MPa greater than atmospheric pressure, a temperature of 650° C. to 750° C., and a duration of 6 to 12 hours. Under these conditions, the lithium aluminum titanium phosphate is conducive to forming a firmly bonded coating layer on the surface of the substrate material, and is conducive to improving the uniformity and density of the coating layer, thereby further improving the rate performance and structural stability of the lithium nickel manganese oxide positive electrode material.

[0082] Compared with the prior art, the preparation method of lithium nickel manganese oxide cathode material provided in this application has the following beneficial effects: 1. Bulk doping modification of the matrix material using M and N elements reduces the content of trivalent Mn, lowers the risk of the Ginger-Taylor effect, thereby effectively reducing the gas production of lithium nickel manganese oxide cathode material and improving the cycle performance and structural stability of lithium nickel manganese oxide cathode material.

[0083] 2. By coating lithium titanium aluminum phosphate onto the surface of the substrate material through a wet coating method, it is beneficial to form a thinner and more uniform and dense coating layer, which can provide more effective protection for the substrate material, act as a physical and chemical barrier, improve the interfacial stability and lithium-ion transport rate between the lithium nickel manganese oxide cathode material and the electrolyte, and thus improve the rate performance of the lithium nickel manganese oxide cathode material.

[0084] 3. The combination of bulk doping with M and N elements and wet coating of lithium titanium aluminum phosphate effectively improves the stability of the surface spinel structure of lithium nickel manganese oxide. Meanwhile, the wet-coated lithium titanium aluminum phosphate can be uniformly and densely bonded with the surface spinel structure of lithium nickel manganese oxide, thus synergistically improving the structural stability and cycle stability of lithium nickel manganese oxide cathode material. This results in a combined improvement in the rate performance, cycle performance, and structural stability of lithium nickel manganese oxide cathode material.

[0085] Furthermore, this application also provides a lithium nickel manganese oxide cathode material prepared by the aforementioned method for preparing lithium nickel manganese oxide cathode material. This lithium nickel manganese oxide cathode material includes a matrix material and a coating layer located on the surface of the matrix material. The matrix material is lithium nickel manganese oxide containing elements M and N. M is a transition metal element with a tetravalent or pentavalent ionic state, and the bond energy of the chemical bond formed by M and oxygen is 350 kJ / mol to 800 kJ / mol. N is a transition metal element with a divalent or trivalent ionic state, and the bond energy of the chemical bond formed by N and oxygen is 350 kJ / mol to 800 kJ / mol. The coating layer is lithium titanium aluminum phosphate, and the general chemical formula of the coating layer is Li. 1+z Al z Ti 2-z (PO4)3, where 0.2≤z≤0.4.

[0086] This lithium nickel manganese oxide cathode material has a spinel structure. On the one hand, the spinel structure can provide high specific capacity, enabling the battery to have a high energy density; on the other hand, it has good structural stability and electrochemical stability, which can provide a long cycle life and stable performance, thus helping to extend the battery's lifespan. At the same time, it has good electrical conductivity, which is conducive to the transport of electrons and ions, improving the battery's performance, reducing internal resistance, and improving the battery's discharge and charge efficiency.

[0087] In some embodiments, the chemical general formula of the matrix material is Li(Li a Ni y Mn x M b N c )O 4-δ , where 0.02 ≤ a ≤ 0.06, 0.04 ≤ b ≤ 0.20, 2 ≤ b / a ≤ 10 / 3, 0 < c ≤ 0.1, 0.4 ≤ y ≤ 0.55, 1.3 ≤ x ≤ 1.6, 0.0001 ≤ δ ≤ 0.05, a + m×b + n×c + 2y + 4x = 7, m is the ionic valence state of element M, and n is the ionic valence state of element N. The matrix material is double-doped with elements M and N in the bulk phase, reducing the content of Mn 3+ , thus reducing the risk of the occurrence of the Jahn-Teller effect, and thus effectively reducing the gas generation amount of the lithium nickel manganese oxide cathode material and improving the cycling performance of the lithium nickel manganese oxide cathode material.

[0088] In some embodiments, M may include at least one of Ti, Zr, Nb, etc., and N may include at least one of Mg, Al, etc. By doping the above elements M and N to modify the lithium nickel manganese oxide cathode material and quantitatively controlling the doping amounts of elements M and N, the gas generation amount of the lithium nickel manganese oxide cathode material can be significantly reduced and the cycling performance of the lithium nickel manganese oxide cathode material can be improved.

[0089] In addition, the surface of the matrix material has a lithium aluminum titanium phosphate coating layer, and the chemical general formula of the coating layer is Li[[ID=二十一]] 1+z [[ID=二十二]]Al[[ID=二十三]] z [[ID=二十四]]Ti[[ID=二十五]] 2-z [[ID=二十六]](PO4)3, where 0.2 ≤ z ≤ 0.4. In terms of structural stability, lithium aluminum titanium phosphate has a stable crystal structure, which can effectively inhibit the volume change of the matrix material during charge and discharge processes, reduce the damage of the lithium nickel manganese oxide cathode material due to structural deformation, and thus improve the cycling stability and structural stability of the lithium nickel manganese oxide cathode material. In terms of chemical stability, lithium aluminum titanium phosphate has good chemical stability, which can effectively block the direct contact between the matrix material and the external electrolyte / electrolyte, reduce the side reactions between the matrix material and the electrolyte, reduce gas generation, and thus improve the cycling performance of the lithium nickel manganese oxide cathode material. In terms of ion transport, lithium aluminum titanium phosphate has good ion conduction performance, which can accelerate the insertion and extraction speed of lithium ions, and is beneficial to improving the rate performance of the lithium nickel manganese oxide cathode material.

[0090] The elements in lithium aluminum titanium phosphate act together. Lithium element, as a key participating element in ion conduction, provides a channel for ion transport; titanium and aluminum elements enhance the structural stability and chemical stability of lithium aluminum titanium phosphate through the optimization of the crystal structure. The synergistic effect of multiple elements enables lithium aluminum titanium phosphate to improve the performance of the lithium nickel manganese oxide cathode material in the above-mentioned multiple aspects when used as a coating layer.

[0091] The coating layer is thin, uniform, and dense, providing more comprehensive protection for the substrate material and acting as a physical and chemical barrier. This improves the interfacial stability and lithium-ion transport rate between the lithium nickel manganese oxide cathode material and the electrolyte, thereby enhancing the rate performance of the lithium nickel manganese oxide cathode material.

[0092] Moreover, the bulk doping of M and N elements is combined with the wet coating of lithium titanium aluminum phosphate. The M and N elements can effectively improve the stability of the surface spinel structure of lithium nickel manganese oxide, and the wet-coated lithium titanium aluminum phosphate can be evenly and densely combined with the surface spinel structure of lithium nickel manganese oxide, synergistically improving the structural stability and cycle stability of the lithium nickel manganese oxide positive electrode material, thereby achieving a joint improvement in the rate performance, cycle performance and structural stability of the lithium nickel manganese oxide positive electrode material.

[0093] In some embodiments, the thickness of the coating layer can be 5 nm to 80 nm, which can provide a more effective physical and chemical barrier for lithium nickel manganese oxide cathode materials and improve the ion transport rate of lithium nickel manganese oxide cathode materials.

[0094] In some embodiments, the charge transfer resistance of the lithium nickel manganese oxide positive electrode material is 15Ω~50Ω, indicating that the interface between the lithium nickel manganese oxide positive electrode material and the electrolyte / electrolyte has good ionic conductivity, which is beneficial to further improve the conductivity of the lithium nickel manganese oxide positive electrode material and accelerate the lithium ion transfer rate. Exemplarily, the charge transfer resistance of the lithium nickel manganese oxide positive electrode material can be 15Ω, 20Ω, 25Ω, 30Ω, 35Ω, 40Ω, 45Ω, 50Ω or any value within the range of any two of the above values. The charge transfer resistance of the lithium manganese oxide positive electrode material can further be 15Ω~30Ω.

[0095] In some embodiments, the average particle size D50 of the lithium nickel manganese oxide cathode material is 3μm~8μm, which is beneficial to improving the compaction density and specific surface area of ​​the lithium nickel manganese oxide cathode material, thereby improving the energy density and charge / discharge reaction activity of the lithium nickel manganese oxide cathode material.

[0096] In some embodiments, the lithium nickel manganese oxide cathode material is a monocrystalline lithium nickel manganese oxide cathode material. Compared to relatively polycrystalline lithium nickel manganese oxide cathode materials, monocrystalline lithium nickel manganese oxide cathode materials have fewer grain boundaries, reducing the occurrence of side reactions, exhibiting better structural stability and high-temperature resistance, and significantly improving the safety of lithium batteries.

[0097] Compared with the prior art, the lithium nickel manganese oxide positive electrode material provided in the embodiment of the present application has the following beneficial effects: 1. The lithium nickel manganese oxide cathode material has a matrix material doped with M and N elements. The transition metal element M with a tetravalent or pentavalent ion state and the transition metal element N with a divalent or trivalent ion state occupy the 16d site by replacing Mn and forming a strong chemical bond with oxygen, thereby reducing the Mn with the Jiang-Taylor effect. 3+ The nitrogen element can also replace nickel and form a strong chemical bond with oxygen, improving the structural stability and cycle performance of the lithium nickel manganese oxide cathode material.

[0098] 2. The lithium nickel manganese oxide positive electrode material also has a coating layer containing lithium titanium aluminum phosphate. The coating layer is thin, uniform and dense, which can provide more comprehensive protection for the base material, act as a physical and chemical barrier, and improve the interface stability and lithium ion transmission rate between the lithium nickel manganese oxide positive electrode material and the electrolyte, thereby improving the rate performance of the lithium nickel manganese oxide positive electrode material.

[0099] 3. The combination of bulk doping with M and N elements and wet coating of lithium titanium aluminum phosphate effectively improves the stability of the surface spinel structure of lithium nickel manganese oxide. Meanwhile, the wet-coated lithium titanium aluminum phosphate can be uniformly and densely bonded with the surface spinel structure of lithium nickel manganese oxide, thus synergistically improving the structural stability and cycle stability of lithium nickel manganese oxide cathode material. This results in a combined improvement in the rate performance, cycle performance, and structural stability of lithium nickel manganese oxide cathode material.

[0100] An embodiment of the present application provides an electrochemical device, which includes a positive electrode plate. The positive electrode plate includes a positive electrode material, and the positive electrode material is the aforementioned lithium nickel manganese oxide positive electrode material.

[0101] Compared with the prior art, the electrochemical device provided in the embodiment of the present application uses the aforementioned lithium nickel manganese oxide positive electrode material, which can effectively improve the high-rate performance of the electrochemical device while ensuring the cycle performance of the electrochemical device.

[0102] The lithium nickel manganese oxide positive electrode material, its preparation method and electrochemical device are further described below through specific examples.

[0103] According to the chemical composition shown in Table 1 and the following steps, the lithium nickel manganese oxide positive electrode materials in Examples 1-3 and Comparative Examples 1-5 were prepared respectively: Example 1 Step 1, according to the chemical formula Li(Li 0.06 Ni 0.47 Mn 1.39 Ti 0.1 Mg 0.02 )O4-δ Weigh a certain amount of lithium carbonate, manganese manganese tetroxide, nickel oxide, Ti oxide (doping element M), and Mg oxide (doping element N) in the molar ratio of each element in the mixture. After wet mixing these materials, the slurry is pulverized using a sand mill to obtain a first mixture with a particle size D50 of 1.0 μm. The first mixture is then spray-dried using a spray dryer to control the moisture content of the first mixture to less than or equal to 1 wt%.

[0104] Step 2: Then, the first mixture is placed in an atmospheric atmosphere with a pressure greater than atmospheric pressure by 0.12 MPa for the first heat treatment: first, it is calcined at 900℃ for 12 hours, and then cooled to 650℃ at a cooling rate of 2℃ / min and held for 8 hours for annealing and oxygen repair. The heat-treated material is then subjected to air jet milling, classification, and sieving to obtain an uncoated matrix material with a particle size D50 of 5.0 μm.

[0105] Step 3: The matrix material and lithium titanium aluminum phosphate are added to water at a mass ratio of 200:1 and wet-mixed using a high-speed mixer at a frequency of 40Hz for 1 hour. Then, the mixture is spray-dried to obtain a second mixture. The spray drying process is performed at a spray rate of 3L / min, a temperature of 280℃, a nozzle pressure of 0.10MPa, and a nozzle diameter of 1.0mm. The preparation of lithium titanium aluminum phosphate includes: according to the chemical formula Li... 1.3 Al 0.3 Ti 1.7 The molar ratio of each element in (PO4)3 is as follows: a certain amount of lithium carbonate, aluminum oxide, titanium oxide, and 85% industrial-grade phosphoric acid solution are weighed and evenly mixed, and then the slurry is crushed with a sand mill to a D50 of 0.5μm~1μm. After spray drying, the moisture content is controlled at ≤1wt%, and then placed in an atmosphere with a pressure greater than 0.12Mpa of atmospheric pressure, calcined at 850℃ for 10h, cooled at 2℃ / min, and then crushed with air flow to obtain lithium aluminum titanium phosphate with an average particle size D50 of 0.5μm.

[0106] Step 4: Perform a second heat treatment on the second mixture to form a coating layer containing lithium titanium aluminum phosphate on the surface of the matrix material. The atmosphere for the second heat treatment is an atmospheric atmosphere with a pressure greater than atmospheric pressure by 0.12 MPa, the temperature is 700℃, the time is 8h, and after cooling at 2℃ / min, the mixture is pulverized by airflow, classified and sieved to obtain lithium nickel manganese oxide cathode material with an average particle size D50 of 5.0μm.

[0107] Example 2 The difference from Example 1 is that in step 1, according to the chemical formula Li (Li 0.06 Ni 0.47 Mn 1.39 Ti 0.1 Mg 0.02)O 4-δ The molar ratio of each element in the raw materials was weighed, and the chemical formula of the prepared matrix material was Li(Li) 0.06 Ni 0.47 Mn 1.39 Ti 0.1 Mg 0.02 )O 4-δ In step 3, the chemical formula of the prepared lithium aluminum titanium phosphate is Li 1.4 Al 0.4 Ti 1.6 (PO4) 3. The other steps are basically the same as those in Example 1, please refer to Example 1.

[0108] Example 3 The difference from Example 1 is that in step 1, according to the chemical formula Li(Li 0.06 Ni 0.47 Mn 1.39 Zr 0.1 Mg 0.02 )O 4-δ The raw materials are weighed in the molar ratio of each element in the matrix material, and the chemical formula of the prepared matrix material is Li(Li 0.06 Ni 0.47 Mn 1.39 Zr 0.1 Mg 0.02 )O 4-δ The other steps are basically the same as in Example 1; please refer to Example 1.

[0109] Comparative Example 1 Step 1, according to the chemical formula Li(Li 0.06 Ni 0.49 Mn 1.49 )O 4-δ A certain amount of lithium carbonate, manganese manganese oxide, and nickel oxide were weighed in the molar ratio of each element in the mixture. After wet mixing the above materials, the slurry was crushed using a sand mill to obtain a mixture with a particle size D50 of 1.0 μm. The mixture was then spray dried using a spray dryer to control the moisture content of the mixture to less than or equal to 1 wt%.

[0110] Step 2: The mixture is then placed in an atmosphere with a pressure greater than 0.12 MPa of atmospheric pressure for a first heat treatment: first calcined at 900°C for 12 hours, then cooled to 650°C at a cooling rate of 2°C / min and kept warm for 8 hours for annealing and oxygen repair. The heat-treated material is crushed by air flow, classified, and sieved to obtain an undoped and uncoated lithium nickel manganese oxide positive electrode material with a particle size D50 of 5.0 μm.

[0111] Comparative Example 2 Step 1, according to the chemical formula Li(Li 0.06 Ni 0.49 Mn1.49 )O 4-δ A certain amount of lithium carbonate, manganese manganese oxide, and nickel oxide were weighed according to the molar ratio of each element in the mixture. After wet mixing the above materials, the slurry was pulverized using a sand mill to obtain a first mixture with a particle size D50 of 1.0 μm. The first mixture was then spray dried using a spray dryer to control the moisture content of the first mixture to be less than or equal to 1 wt%.

[0112] Step 2: The first mixture is then placed in an atmosphere with a pressure greater than 0.12 MPa of atmospheric pressure for a first heat treatment: first calcined at 900°C for 12 hours, then cooled to 650°C at a cooling rate of 2°C / min and kept warm for 8 hours for annealing and oxygen repair. The heat-treated material is crushed by air flow, classified, and sieved to obtain an undoped matrix material with a particle size D50 of 5.0 μm.

[0113] Step 3: The base material and lithium aluminum titanium phosphate are wet mixed with water in a high-speed mixer at a mass ratio of 200:1. The high-speed wet mixing is performed at a frequency of 40 Hz for 1 hour, and then spray dried to obtain a second mixture. The spray drying spray rate is 3 L / h, the temperature is 280 ° C, the nozzle pressure is 0.10 MPa, and the nozzle diameter is 1.0 mm. The preparation of lithium aluminum titanium phosphate includes: 1.3 Al 0.3 Ti 1.7 The molar ratio of each element in (PO4)3 is as follows: a certain amount of lithium carbonate, aluminum oxide, titanium oxide, and 85% industrial-grade phosphoric acid solution are weighed and evenly mixed, and then the slurry is crushed with a sand mill to a D50 of 0.5μm~1μm. After spray drying, the moisture content is controlled at ≤1wt%, and then placed in an atmosphere with a pressure greater than 0.12Mpa of atmospheric pressure, calcined at 850℃ for 10h, cooled at 2℃ / min, and then crushed with air flow to obtain lithium aluminum titanium phosphate with an average particle size D50 of 0.5μm.

[0114] Step 4, performing a second heat treatment on the second mixture to form a coating layer containing lithium titanium aluminum phosphate on the surface of the base material. The atmosphere of the second heat treatment is an atmospheric atmosphere with a pressure greater than 0.12 MPa of atmospheric pressure, the temperature is 700°C, and the time is 8 hours. After cooling at 2°C / min, the mixture is crushed by air flow and graded sieved to obtain a lithium nickel manganese oxide positive electrode material with an average particle size D50 of 5.0 μm, which is not doped with M and N elements but has a lithium titanium aluminum phosphate coating layer.

[0115] Comparative Example 3 Step 1, according to the chemical formula Li(Li 0.06 Ni 0.49 Mn 1.39 Ti 0.1 )O 4-δWeigh a certain amount of lithium carbonate, manganese manganese tetroxide, nickel oxide, and Ti (doping element M) oxide in the molar ratio of each element in the mixture. After wet mixing the above materials, the slurry is pulverized using a sand mill to obtain a mixture with a particle size D50 of 1.0 μm. The mixture is then spray-dried using a spray dryer to control the moisture content of the first mixture to less than or equal to 1 wt%.

[0116] Step 2: The mixture is then placed in an atmosphere with a pressure greater than 0.12 MPa of atmospheric pressure for a first heat treatment: first calcined at 900°C for 12 hours, then cooled to 650°C at a cooling rate of 2°C / min and kept warm for 8 hours for annealing and oxygen repair. The heat-treated material is crushed by air flow, classified, and sieved to obtain a single-doped M element lithium nickel manganese oxide positive electrode material with a particle size D50 of 5.0 μm and no coating.

[0117] Comparative Example 4 Step 1, according to the chemical formula Li(Li 0.06 Ni 0.47 Mn 1.39 Ti 0.1 Mg 0.02 )O 4-δ Weigh a certain amount of lithium carbonate, manganese manganese tetroxide, nickel oxide, Ti (doping element M) oxide, and Mg (doping element N) oxide according to the molar ratio of each element in the mixture. After wet mixing these materials, the slurry is pulverized using a sand mill to obtain a mixture with a particle size D50 of 1.0 μm. The mixture is then spray-dried using a spray dryer to control the moisture content of the mixture to less than or equal to 1 wt%.

[0118] Step 2: The mixture is then placed in an atmosphere with a pressure greater than 0.12 MPa of atmospheric pressure for a first heat treatment: first calcined at 900°C for 12 hours, then cooled to 650°C at a cooling rate of 2°C / min and kept warm for 8 hours for annealing and oxygen repair. The heat-treated material is crushed by air flow, classified, and sieved to obtain a lithium nickel manganese oxide positive electrode material doped with M and N elements but not coated with a particle size D50 of 5.0 μm.

[0119] Comparative Example 5 Step 1, according to the chemical formula Li(Li 0.06 Ni 0.47 Mn 1.39 Ti 0.1 Mg 0.02 )O 4-δWeigh a certain amount of lithium carbonate, manganese manganese tetroxide, nickel oxide, Ti oxide (doping element M), and Mg oxide (doping element N) in the molar ratio of each element in the mixture. After wet mixing these materials, the slurry is pulverized using a sand mill to obtain a first mixture with a particle size D50 of 1.0 μm. The first mixture is then spray-dried using a spray dryer to control the moisture content of the first mixture to less than or equal to 1 wt%.

[0120] Step 2: The first mixture is then placed in an atmosphere with a pressure greater than 0.12 MPa of atmospheric pressure for a first heat treatment: first calcined at 900°C for 12 hours, then cooled to 650°C at a cooling rate of 2°C / min and kept warm for 8 hours for annealing and oxygen repair. The heat-treated material is crushed by air flow, classified, and sieved to obtain an uncoated base material with a particle size D50 of 5.0 μm.

[0121] Step 3: dry-mix and coat the matrix material and lithium aluminum titanium phosphate in a mass ratio of 200:1 using a high-speed mixer, and mix at a high speed of 40 Hz for 1 hour. 1.3 Al 0.3 Ti 1.7 The molar ratio of each element in (PO4)3 is as follows: a certain amount of lithium carbonate, aluminum oxide, titanium oxide, and 85% industrial-grade phosphoric acid solution are weighed and evenly mixed, and then the slurry is crushed with a sand mill to a D50 of 0.5μm~1μm. After spray drying, the moisture content is controlled at ≤1wt%, and then placed in an atmosphere with an atmospheric pressure greater than 0.12Mpa of atmospheric pressure, calcined at 850℃ for 10h, cooled at 2℃ / min, and then crushed with air flow to obtain lithium aluminum titanium phosphate with an average particle size D50 of 0.5μm.

[0122] Step 4: Perform a second heat treatment on the second mixture to form a coating layer containing lithium titanium aluminum phosphate on the surface of the base material. The atmosphere of the second heat treatment is an atmospheric atmosphere with a pressure greater than 0.12 MPa of atmospheric pressure, a temperature of 700°C, and a time of 8 hours. After cooling at 2°C / min, the mixture is crushed by air flow and graded sieved to obtain a lithium nickel manganese oxide positive electrode material with an average particle size D50 of 5.0 μm.

[0123] The following tests were performed on the lithium nickel manganese oxide positive electrode materials obtained in Examples 1-3 and Comparative Examples 1-5.

[0124] (1) Scanning electron microscopy (SEM) test: A JEC JCM 6000 scanning electron microscope (SEM) was used. This instrument has high-resolution imaging capabilities and can clearly observe the microscopic morphology and structural characteristics of the cathode material. The acceleration voltage is 10.00 kV and the magnification is 5000 times.

[0125] (2) X-ray diffraction (XRD) analysis: the test step size was 0.02°, the scanning speed was 2° / min, and the scanning angle was 14~80°.

[0126] (III) The electrical performance test conditions are as follows: SP: PVDF: lithium nickel manganese oxide positive electrode materials are evenly mixed in a mass ratio of 5:3:2 to make a CR2025 button battery. The compaction density of the positive electrode sheet is 3.0~3.2g / cm 3 .

[0127] Capacity test and cycle performance test: Under the test conditions of operating voltage 3~4.9V, charge and discharge rates of 0.1C / 0.1C and 0.2C / 5C, and charging CV cut-off current of 0.01C, the room temperature capacity at 0.1C and 5C and the 100-cycle 1C cycle retention rate at 45℃ are tested.

[0128] "Shoulder capacity ratio": This refers to the ratio of capacity (3.0~4.3V) to capacity (3.0~4.9V) under 0.1C discharge conditions. The lower the "shoulder capacity ratio", the lower the capacity contribution of the disordered phase of lithium nickel manganese oxide.

[0129] Charge transfer resistance (Rct) testing: Electrochemical impedance spectroscopy (EIS) is an important electrochemical method for studying electrode reaction kinetics and electrode interface phenomena. It uses a small-amplitude sinusoidal potential as the perturbation signal. Charge transfer resistance (Rct) was measured on a Solartron EnergyLab XM electrochemical tester using the aforementioned CR2025 button cell. The AC excitation signal amplitude was ±5mV, the measured frequency range was 0.01-100,000Hz, and the test temperature was 25±2°C. The button cell was activated at 0.1C for the first cycle and then rested for ≥4 hours before testing.

[0130] Gas production test: Gas production in a fully charged 2Ah soft-pack battery made with lithium nickel manganese oxide (LMN) cathode material after storage at 45°C for 7 days was measured using the immersion volumetric method (a solvent displacement method based on Archimedes' principle). The gas production per unit amount of cathode active material (mL / g) was calculated based on the obtained gas production and the amount of cathode active material in the cathode sheet.

[0131] (IV) Ionic conductivity test of coated lithium titanium aluminum phosphate powder: The blocking electrode + Eis test method is used, and the calculation is performed by σ=d / RS, where σ is the ionic conductivity, in S / cm; d is the thickness of lithium titanium aluminum phosphate, in cm; R is the impedance value of lithium titanium aluminum phosphate measured by the electrochemical workstation, in Ω; S is the surface area of ​​lithium titanium aluminum phosphate, in cm 2 .

[0132] The relevant test results of Examples 1-3 and Comparative Examples 1-5 are shown in Tables 2 and 3.

[0133] The above results show that: Figure 3 The image shows a SEM image of the lithium nickel manganese oxide cathode material prepared in Example 1, which has both metal element co-doping and wet coating to form a lithium titanium aluminum phosphate coating. Figure 4 The image shows a SEM image of the lithium nickel manganese oxide cathode material prepared in Comparative Example 4, which is co-doped with only metal elements. Figure 5 This is an SEM image of the lithium nickel manganese oxide positive electrode material prepared in Comparative Example 5, which has both metal element co-doping and a lithium aluminum titanium phosphate coating layer formed by solid phase coating. The final product morphology of Example 1 and Comparative Examples 4-5 is all single crystal particles, indicating that the preparation process of Example 1 of the present application can produce a single crystal lithium nickel manganese oxide positive electrode material with fewer grain boundaries, better structural stability and high temperature resistance. In addition, in Comparative Example 5, dry coating was used, and the coating layer formed had point-like, island-like, overly thick or uneven phenomena. In contrast, in Example 1, due to the wet coating method, the coating layer formed after sintering has the advantages of being thin, uniform and dense.

[0134] Figure 6 The XRD patterns of Examples 1-3 and Comparative Examples 1-5 show that all of them form lithium nickel manganese oxide phases without impurity peaks.

[0135] It can be seen from Table 2 combined with Table 3 that compared with Comparative Examples 1-5, the capacity and cycle performance of the batteries prepared from the lithium nickel manganese oxide positive electrode materials in Examples 1-3 have been effectively improved. Among them, at a rate of 0.1C, the discharge capacity of the corresponding batteries of Examples 1-3 is higher than 133mAh / g, and the discharge capacity at a high rate of 5C is higher than 131mAh / g. The volume retention rate after 100 cycles is also as high as 96%. However, the 1C discharge capacity of the corresponding batteries of Comparative Examples 1-5 is lower than that of Examples 1-3, and the 5C discharge capacity is lower than 130mAh / g. The volume retention rate after 100 cycles is only 93%. Moreover, the charge transfer resistance values ​​of the lithium nickel manganese oxide positive electrode materials in Examples 1-3 are all below 20Ω, indicating that the wet coating of lithium aluminum titanium phosphate improves the interface performance between the lithium nickel manganese oxide positive electrode material and the electrolyte, optimizes the charge transfer process at the electron / ion conductive junction, thereby improving the lithium ion transfer rate and rate performance of the lithium nickel manganese oxide positive electrode material. In addition, the gas production of Examples 1-3 was also effectively reduced, from 123 mL / g in Comparative Example 1 to approximately 65 mL / g. This indicates that bulk doping with M and N elements and wet coating with lithium aluminum titanium phosphate, which has high ionic conductivity, can form a synergistic effect, effectively improving the rate performance and cycle performance of the lithium nickel manganese oxide positive electrode material, while reducing gas production, thereby improving the stability of the lithium nickel manganese oxide positive electrode material.

[0136] Among them, by comparing Comparative Example 1 with Comparative Example 2, it can be seen that wet coating of lithium aluminum titanium phosphate can improve the power, cycle and storage performance (low gas production) of lithium nickel manganese oxide positive electrode materials. By comparing Comparative Example 1 with Comparative Example 3, it can be seen that doping with Ti, a high-valent metal at the 16d position of Mn, can improve the power, cycle and storage performance (low gas production) of lithium nickel manganese oxide. By comparing Comparative Example 3 with Comparative Example 4, it can be seen that doping with Mg, a low-valent metal at the 16d position of Mn, can improve the cycle and storage performance (low gas production) of lithium nickel manganese oxide positive electrode materials. By comparing Example 1 with Comparative Example 5, it can be seen that compared with dry coating, wet coating can not only improve the morphology of the coating layer, but also increase the density of the coating layer, thereby improving the rate performance of the lithium nickel manganese oxide positive electrode material. By comparing Example 1 with Comparative Examples 2 and 4, it can be seen that the use of M and N elements for doping and wet coating of lithium titanium aluminum phosphate can form a synergistic effect, thereby improving the rate performance of the lithium nickel manganese oxide positive electrode material, improving the cycle performance of the lithium nickel manganese oxide positive electrode material, reducing gas production, and improving the stability of the lithium nickel manganese oxide positive electrode material.

[0137] In addition, compared with comparative examples 1-5, the “shoulder capacity ratio” of examples 1-3 decreased, and the shoulder capacity was mainly caused by Mn 3+ Contribution, the capacity contribution ratio of the disordered phase of the lithium nickel manganese oxide positive electrode material is reduced, indicating that the Mn 3+ The content is reduced by doping with metal elements, thereby reducing the Mn 3+Moreover, due to the coating of lithium aluminum titanium phosphate, the dissolution of doping elements is reduced, the doping effect is improved, and the Mn 3+ content.

[0138] It can be seen that Examples 1-3 of the present application form a matrix material of a lithium nickel manganese oxide positive electrode material of a specific chemical composition by co-doping M and N elements during the preparation process, which not only reduces the occurrence of the Jan-Taylor effect, ensures the structural stability and capacity of the material, but also improves the cycle performance and storage performance of the material. Combined with the lithium titanium aluminum phosphate coating layer formed by wet coating, it acts as a physical and chemical barrier, reduces the dissolution of the doping elements M and N, and improves the interface stability and lithium ion transfer rate between the lithium nickel manganese oxide positive electrode material and the electrolyte, thereby improving the rate performance of the lithium nickel manganese oxide positive electrode material. The embodiments of the present application combine element doping with lithium titanium aluminum phosphate wet coating, which can synergistically construct a conductive network and improve structural stability, thereby achieving a joint improvement in the rate performance, cycle performance and structural stability of the lithium nickel manganese oxide positive electrode material.

[0139] It will be understood that the above embodiments are merely exemplary embodiments for illustrating the principles of the present invention, and the present invention is not limited thereto. Those skilled in the art will appreciate that various modifications and improvements can be made without departing from the spirit and substance of the present invention, and such modifications and improvements are also considered to be within the scope of protection of the present invention.

Claims

1. A method for preparing a lithium nickel manganese oxide positive electrode material, characterized in that: The preparation method comprises: Mixing a nickel source, a manganese source, a first compound, a second compound and a lithium source to obtain a first mixture, wherein the first compound contains an M element, the M element is a transition metal element with a tetravalent or pentavalent ion state, and the bond energy of a chemical bond formed by the M element and oxygen is 350 kj / mol to 800 kj / mol, and the second compound contains an N element, the N element is a transition metal element with a divalent or trivalent ion state, and the bond energy of a chemical bond formed by the N element and oxygen is 350 kj / mol to 800 kj / mol; performing a first heat treatment on the first mixture to obtain a matrix material; Wet-mixing the matrix material with lithium aluminum titanium phosphate, and spray-drying the mixture to obtain a second mixture; and The second mixture is subjected to a second heat treatment to form a coating layer on the surface of the base material, wherein the coating layer has a chemical formula of Li 1+z Al z Ti 2-z (PO4)3, 0.2≤z≤0.4, thereby obtaining the lithium nickel manganese oxide positive electrode material.

2. The method for preparing the lithium nickel manganese oxide positive electrode material according to claim 1, characterized in that: The stirring frequency of the wet mixing is 10 Hz to 50 Hz; and / or The stirring time of the wet mixing is 0.5h~10h.

3. The method for preparing the lithium nickel manganese oxide positive electrode material according to claim 1, characterized in that: The spray drying satisfies at least one of the following conditions: (1) The spray drying spray rate is 1L / h~10L / h; (2) The spray drying temperature is 250°C to 300°C; (3) The nozzle pressure of the spray drying is 0.05MPa~0.2MPa; (4) The diameter of the spray drying nozzle is 0.5 mm to 2 mm.

4. The method for preparing the lithium nickel manganese oxide positive electrode material according to claim 1, characterized in that: The mass ratio of the matrix material to the lithium aluminum titanium phosphate is (0.1-5):1; and / or The general formula of the matrix material is Li(Li a Ni y Mn x M b N c )O 4-δ , where 0.02 ≤ a ≤ 0.06, 0.04 ≤ b ≤ 0.20, 2 ≤ b / a ≤ 10 / 3, 0 < c ≤ 0.1, 0.4 ≤ y ≤ 0.55, 1.3 ≤ x ≤ 1.6, 0.0001 ≤ δ ≤ 0.05, a + m×b + n×c + 2y + 4x = 7, m is the ionic valence of element M, and n is the ionic valence of element N.

5. The method for preparing the lithium nickel manganese oxide positive electrode material according to claim 1, characterized in that: The conditions of the second heat treatment include: the atmosphere includes an atmosphere pressure greater than the atmospheric pressure by 0.05MPa~0.2MPa, the temperature is 650℃~750℃, and the time is 6h~12h.

6. The method for preparing a lithium nickel manganese oxide positive electrode material according to claim 1, characterized in that: The preparation method of lithium aluminum titanium phosphate comprises: Mixing an Al-containing compound, a Ti-containing compound, a P-containing compound and a Li-containing compound and spray drying the mixture to obtain a coating material precursor; and The coating material precursor is subjected to a third heat treatment to obtain the lithium aluminum titanium phosphate.

7. A lithium nickel manganese oxide positive electrode material, characterized in that: The method for preparing a lithium nickel manganese oxide positive electrode material according to any one of claims 1 to 6, wherein the lithium nickel manganese oxide positive electrode material comprises a base material and a coating layer located on the surface of the base material, wherein the base material is lithium nickel manganese oxide containing an M element and an N element, wherein the M element is a transition metal element with a tetravalent or pentavalent ion state, and the bond energy of the chemical bond formed by the M element and oxygen is 350 kj / mol to 800 kj / mol, the N element is a transition metal element with a divalent or trivalent ion state, and the bond energy of the chemical bond formed by the N element and oxygen is 350 kj / mol to 800 kj / mol, and the general chemical formula of the coating layer is Li 1+z Al z Ti 2-z (PO4)3, where 0.2≤z≤0.

4.

8. The lithium nickel manganese oxide positive electrode material according to claim 7, characterized in that: The coating layer has a thickness of 5 nm to 80 nm; and / or The charge transfer resistance value of the lithium nickel manganese oxide positive electrode material is 15Ω~50Ω.

9. The lithium nickel manganese oxide positive electrode material according to claim 7, characterized in that: The chemical general formula of the matrix material is Li(Li a Ni y Mn x M b N c )O 4-δ , where 0.02 ≤ a ≤ 0.06, 0.04 ≤ b ≤ 0.20, 2 ≤ b / a ≤ 10 / 3, 0 < c ≤ 0.1, 0.4 ≤ y ≤ 0.55, 1.3 ≤ x ≤ 1.6, 0.0001 ≤ δ ≤ 0.05, a + m×b + n×c + 2y + 4x = 7, m is the ionic valence state of the M element, and n is the ionic valence state of the N element.

10. An electrochemical device, characterized in that: The electrochemical device comprises a positive electrode sheet, the positive electrode sheet comprises a positive electrode material, and the positive electrode material is the lithium nickel manganese oxide positive electrode material as described in any one of claims 7 to 9.

Citation Information

Cited By

  • Preparation method and application of lithium manganate positive electrode material coated with super-ionic conductor material

    CN122224815A